Global Positive Periodic Solutions for Periodic Two-Species Competitive Systems with Multiple Delays and Impulses - Zhenguo Luo; Liping Luo; Liu Yang; Yunhui Zeng (Abstract and Applied Analysis)
A set of easily verifiable sufficient conditions are derived to guarantee the existence and the global stability of positive periodic solutions for two-species competitive systems with multiple delays and impulses, by applying some new analysis techniques. This improves and extends a series of the well-known sufficiency theorems in the literature about the problems mentioned previously.